FAMILY SUPPORT AND DIABETES SELF-MANAGEMENT PROGRAM FOR TYPE 2 DIABETES MELLITUS : SYSTEMATIC REVIEW - Anih Kurnia (LP3M Universitas Muhammadiyah Tasikmalaya, 2022)
Background: Diabetes mellitus is a global health problem and is the 7th leading cause of death worldwide. Self-management has become a central concept for diabetics who are in families. The purpose of this to review and describe the impact of family support and self-management programs by involving families with health behavior outcomes in patients, namely self-management behavior, psychological results, and clinical outcomes consisting of body mass index, blood pressure, cholesterol levels, and sugar blood control. Methods: Searches were made on three databases, Science Direct, Google Scholar, and Pub Med from 2010-2020. In total, 22 studies met the inclusion criteria. Results: Twenty-two articles examined the impact of self-management programs on diabetes with family involvement. Based on this literature review, engagement using a collaborative approach can influence the patient's self-management behavior so that it changes the patient's health behavior and changes the clinical outcome in an optimal state. They experience obstacles due to the lack of information they have. The follow-up strategy is considered effective in measuring the success of the intervention. Conclusion, from this review, that diabetes self-management programs with family support can improve health outcomes in patients with controlled blood sugar levels.